Book Review: Dead Aid: Why Aid Is Not Working and There Is Another Way for Africa by Dambisa Moyo. (20th February 2013) - Ashta, Arvind
Abstract Dambisa Moyo, Dead Aid: Why Aid Is Not Working and There Is Another Way for Africa, Penguin Books, London, 2009, 188 pages.